Fingolimod and risk of skin cancer among individuals with multiple sclerosis: a population-based cohort study protocol - Lisa Kuramoto; Larry D Lynd; Amir Khakban; Jacquelyn J Cragg; Anthony Traboulsee; Jiwon Oh; Analisa Jia; Weng Sut Sio; M A De Vera; Jonathan Loree; Roger Tam (BMJ Open)
Introduction Long-term population-based safety studies, applying advanced causal inference techniques, including an active comparator with new-user design, are needed to investigate skin cancer outcomes among individuals with multiple sclerosis (MS) treated with fingolimod. This study aims to describe a protocol for investigating the relationship between fingolimod use and the incidence of skin cancer among individuals with MS.Methods and analysis We will use population-based administrative health data from two Canadian provinces (British Columbia and Alberta) to conduct an observational cohort ‘trial emulation’ study with an active comparator and new-user design. Individuals with MS aged ≥18 years will be identified using a validated algorithm. Incident users of fingolimod and active comparators (natalizumab, alemtuzumab, dimethyl fumarate, teriflunomide) will then be identified. The outcome of interest will be skin cancer (melanoma and non-melanoma skin cancers). Survival analysis will be used to estimate HRs and corresponding 95% CIs, adjusted for potential confounders.Ethics and dissemination Ethics approval for this study was obtained from the University of British Columbia Clinical Research Ethics Board (H24-03199). No personal identifying information will be made available as part of this study. Findings will be disseminated through presentations and peer-reviewed publications.Trial registration number NCT06705608.